Fundamentals of Business Process Management - Dumas, Marlon; Rosa, Marcello La; Mendling, Jan; Reijers, Hajo A. (Springer, 2013)
Business Process Management (BPM) is a special field for more than one reason. First of all, BPM is a crossroad of multiple, quite different viewpoints. Business managers are attracted to BPM because of its demonstrated ability to deliver improvements in organizational performance, regulatory compliance and service quality. Industrial engineers see BPM as an opportunity to apply well-trodden manufacturing optimization techniques in the context of organizations that deliver services rather than physical products. Finally, Information Technology (IT) specialists appreciate the fact that BPM provides them with a shared language to communicate with business stakeholders. Furthermore, business process automation technology allows IT specialists to implement and monitor IT systems in a way that is aligned with the vision that business stakeholders have of the organization. In other words, BPM is a boundary-spanning field that serves as a melting pot for otherwise separate communities. For those who have experienced how business managers, industrial engineers and IT professionals often seem to live in different worlds, this shared field of interest is a remarkable opportunity to achieve a joint understanding of the inner workings of a business. A second special characteristic of BPM is that it is both actively practiced and actively researched. In other words, it is a field where there are both proven and established practices as well as open challenges. Businesses around the world are carrying out BPM initiatives with the aim to, for example, outperform their competitors or meet the demands of regulatory authorities. Academics in fields like computer science, management science, sociology, and engineering are working on the development of methods and techniques to support such initiatives. It is appropriate to see BPM as a “theory in practice” field. On the one hand, practical demands inspire the development of new methods and technologies. On the other hand, the application of these methods and technologies in practice feeds back to the drawing boards in universities and research centers.